Actinomycosis of the omentum with invasion of the abdominal wall, small bowel and transverse colon mimicking malignancy. Issue 1 (28th January 2019) - Caplan, Edward; Deputy, Mohammed; Arul, Dhili; Wilson, Jonathan
Abstract : We report the case of a 59-year-old Russian man who presented with a painless, slow-growing, epigastric mass. CT revealed a large heterogeneous mass within the omentum infiltrating into adjacent tissues. During diagnostic laparoscopy, the omental mass was noted to be firm, raising the suspicion of malignancy. Surgical en-bloc resection of the mass, including the posterior rectus sheath, transverse colon and small bowel, was performed with primary anastomoses at laparotomy. Histological examination was inconsistent with malignancy and revealed the mass to be actinomycosis, confirmed by microscopy and gram staining. Surgical resection was followed by an 8-week course of penicillin and doxycycline antibiotic therapy. This treatment resulted in full clinical and radiological recovery with no complications. Although the clinical and radiological findings, in this case, were highly suspicious of malignancy, abdominal actinomycosis should be considered a differential diagnosis in patients with infiltrative abdominal masses and mild constitutional symptoms.